2020
DOI: 10.17577/ijertv9is080192
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Stir Cast Process Parameters for Better Mechanical Properties

Abstract: Stir casting for HMMC fabrication is known to defeat the defects that acquire during the conventional casting processes. The near-net shape manufacturing ability and potential to yield higher hardness are the capability of the stir casting provided technical parameters are accurately controlled. In this research, optimization technique for stir casting process parameter is established by Taguchi technique to explore the correlation among the hardness and tensile strength. Three different process parameters nam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Kumar and Kumar (2017) investigated the influence of stir process parameters such as reinforcement fraction, stirring speed, processing temperature, and stirring speed on tensile strength, hardness, and impact energy in stir cast AA6063 metal matrix composites using the Taguchi approach. Patil and Patil (2020) investigated the effect of stir-casting process parameters such as stirring time, processing temperature, and stirring speed on the mechanical properties of Al6061 alloy and SiC/Gr 5 wt% each using the Taguchi technique.…”
Section: Introductionmentioning
confidence: 99%
“…Kumar and Kumar (2017) investigated the influence of stir process parameters such as reinforcement fraction, stirring speed, processing temperature, and stirring speed on tensile strength, hardness, and impact energy in stir cast AA6063 metal matrix composites using the Taguchi approach. Patil and Patil (2020) investigated the effect of stir-casting process parameters such as stirring time, processing temperature, and stirring speed on the mechanical properties of Al6061 alloy and SiC/Gr 5 wt% each using the Taguchi technique.…”
Section: Introductionmentioning
confidence: 99%
“…The main effect plot for S/N ratio of microhardness is shown in Figure 4 and Table 5. The larger is better criteria is selected for optimization on stir casting process parameters on microhardness response [20]. The main effect plot for S/N ratio revealed that increasing boron carbide addition increases the microhardness of the AL7050/B 4 C composites.…”
Section: Resultsmentioning
confidence: 99%